Cathodoluminescence of iodine dimers in KCl:I crystals - Korepanov V. I. Vladimir Ivanovich; Vilchinskaya S. S.; Lisitsyn V. M. Viktor Mikhailovich; Kuznetsov M. F. (2005, 2005)
В фонде НТБ ТПУ отсутствует